Ticagrelor does not impact patient‐reported pain in young adults with sickle cell disease: a multicentre, randomised phase IIb study. (16th November 2018) - Kanter, Julie; Abboud, Miguel R.; Kaya, Banu; Nduba, Videlis; Amilon, Carl; Gottfridsson, Christer; Rensfeldt, Martin; Leonsson‐Zachrisson, Maria; ,
Summary: Ticagrelor is an antiplatelet agent for adults with coronary artery disease. The inhibition of platelet activation may decrease the frequency of vaso‐occlusion crisis (VOC) in sickle cell disease (SCD). The HESTIA2 study (NCT02482298) randomised 87 adults with SCD (aged 18–30 years) 1:1:1 to twice‐daily ticagrelor 10, 45 mg or placebo for 12 weeks. Numerical decreases from baseline in mean proportion of days with patient‐reported pain (primary endpoint) were seen in all three groups, as well as in pain intensity and analgesic use, with no significant differences between placebo and ticagrelor treatment groups. Plasma ticagrelor concentrations and platelet inhibition increased with dose. Adverse events were distributed evenly across groups and two non‐major bleeding events occurred per group. Ticagrelor was well tolerated with a low bleeding risk, but no effect on diary‐reported pain was detected. Potential effects on frequency of VOCs will need to be evaluated in a larger and longer study.